ADAPTASI MASYARAKAT PESISIR TERHADAP PERUBAHAN IKLIM - Lora Pelintya, Frischa; Ledyawati (JURNAL ILMIAH IDEA, 2026)
This research aims to analyze how coastal communities, specifically fishermen in Bengkulu’s Pasar Bengkulu, adapt to climate change. The method used is qualitative research with a descriptive approach, where data is collected through observation, interviews, and documentation. This research utilizes the Structural Functionalism theory and the theory of Coastal Community Adaptation to Climate Change by Talcott Parsons and Émile Durkheim, viewing society as a system comprising various interconnected elements or structures that work together to maintain stability and sustainability. Each element (such as family, economy, religion, or other institutions) has a specific function that supports the balance of the social system. When change occurs, society must make adjustments (adaptations) to keep the system stable and functional. The research results show that this adaptation of coastal communities to climate change has great potential for the lives of coastal communities, enabling them to continue their lives under any conditions. The conclusion of the research emphasizes the importance of management strategies and community adaptation strategies to existing climate patterns in Bengkulu’s Pasar Bengkulu, so they can continue to cope with all climate conditions with thorough preparation.